Achievement-motivation and child-rearing in different social contexts - FONTAINE, AM (1994)
This study explores the relationship between achievement motivation at school and child rearing practices. It aims is to discover what aspects of rearing practices differentiate higher and lower motivated pupils and whether these aspects vary with the specificity of life contexts (SES, area of residence) or with the subject gender. Six variables (family life structuring, autonomy, authoritarianism, child acceptance, expectation of success and locus of causality) were assessed through a questionnaire administered to 288 mothers of sixth graders selected from a population of about 4500 pupils. Results show that the more motivated children live in more rigidly structured families than the less motivated. They have less autonomy, with the exception of rural girls from a high SES and urban girls from a low SES who have more autonomy than the less motivated ones. Internal locus of causality is associated with higher motivation in pupils of both sexes from an average SES, in boys from high SES and in girls from a low SES; and with a lower motivation in boys from a low SES and girls from a high SES. No meaningful association was observed between motivation and child acceptance, authoritarianism or success expectation. These results point to the usefulness of research to explore the differential influences of social context and individual gender on the relationship between child rearing practices and pupil's achievement motivation.